IMPLEMENTATION OF THE POSYANDU PROGRAM FOR THE ELDERLY IN GAMPONG LANCOK PANTE ARA, KUALA SUB-DISTRICT, BIREUEN DISTRICT - Urrahmi, Nisa Urrahmi; Aisyah, Ti; Muklir, Muklir; Murniati, Murniati (Jurnal Cakrawala Ilmiah, 2024)
The implementation of the elderly posyandu program in Gampong Lancok Pante Ara is still not going well. This is due to the lack of participation of the elderly to participate in the posyandu program for the elderly which is held once a month. There are 81 pre-elderly and elderly people in Lancok Pante Ara village. Of the number of pre- elderly and elderly people who participated in the elderly posyandu program, only 18 people participated. This is due to the lack of awareness of the importance of health for the elderly and the lack of assistance from the elderly family. The research method used in this research is descriptive qualitative research method. Data collection methods include observation, interviews and documentation. The data analysis techniques include data reduction, data presentation and conclusion drawing. The results showed that the implementation of the posyandu program for the elderly in Gampong Lancok Pante Ara had been carried out according to the SOP, there were three programs carried out, namely the health service program, provision of additional food (PMT) and home visits for the elderly resti. The conclusion in this study is that the implementation of the posyandu program in Gampong Lancok Pante Ara has been carried out by the implementers although it has not been effective due to several factors that hinder the implementation of this posyandu program.